FORMULASI TEPUNG LABU KUNING (Cucurbita maxima) DAN TERIGU TERHADAP DERAJAT PENGEMBANGAN ADONAN DAN SIFAT ORGANOLEPTIK ROTI MANIS - Susilawati Susilawati; Subeki Subeki; Indra Pratama Putra Azis (Teknologi Hasil Pertanian Fakultas Pertanian Universitas Lampung, 2013)
The aim of the research was to determine the formulation of pumpkin flour and wheat flour for producing the best of dough improvement and organoleptic properties of sweet bread. The research was carried out in a complete randomized block design, single factor with 8 treatments and 3 replications. The 8 formulations of pumpkin flour and wheat flour were: (F) consisted of F1 (0:100), F2 (5:95), F3 (10:90), F4 (15:85), F5 (20:80), F6 (25:75), F7 (30:70), and F8 (35:65). The results showed that F3 was the best formulation to produce sweet bread with a dough improvement 2.51% and organoleptic with score of color 4.07 (yellow), texture 3.43 (somewhat soft), taste 3.50 (sweet), flavor 3.00 (somewhat typical pumpkin), and overall acceptance 3.70 (like). The sweet bread of F3 contained moisture 18.90%, ash 1.18%, fat 8.63%, protein 9.47%, crude fiber 3.11%, and carbohydrate (by difference )58.71%. Keywords: Cucurbita maxima, pumpkin flour, sweet bread, wheat flour